2022
DOI: 10.3390/molecules27062019
|View full text |Cite
|
Sign up to set email alerts
|

Hispidulin Ameliorates Endotoxin-Induced Acute Kidney Injury in Mice

Abstract: Lipopolysaccharide (LPS) is an endotoxin that plays a crucial role in septic acute kidney injury (AKI). Hispidulin is a natural flavonoid that possesses various biological activities. Recent studies have shown that hispidulin administration alleviates various inflammatory diseases in animal models. This study aimed to investigate the renoprotective effect of hispidulin on LPS-induced AKI. Male C57BL/6 mice were administered LPS (10 mg/kg) with or without hispidulin (50 mg/kg). Hispidulin administration attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Renal amount of the lipid peroxidation product MDA [ 34 , 35 ] was also reduced by CS (UUO, 6.3 ± 0.6 nmol/mg protein vs. UUO+CS, 3.1 ± 0.4 nmol/mg protein, p < 0.001) ( Figure 5 C). In addition, IF staining for 8-OHdG, an oxidative nucleoside product [ 36 ], revealed that the number of 8-OHdG-positive cells increased after UUO surgery (Sham, 1.1 ± 0.4 vs. UUO, 40.3 ± 4.4, p < 0.001) ( Figure 5 D,E). However, CS treatment remarkably reduced the number of 8-OHdG-positive cells (UUO, 40.3 ± 4.4 vs. UUO+CS, 6.4 ± 1.3, p < 0.001) ( Figure 5 D,E).…”
Section: Resultsmentioning
confidence: 99%
“…Renal amount of the lipid peroxidation product MDA [ 34 , 35 ] was also reduced by CS (UUO, 6.3 ± 0.6 nmol/mg protein vs. UUO+CS, 3.1 ± 0.4 nmol/mg protein, p < 0.001) ( Figure 5 C). In addition, IF staining for 8-OHdG, an oxidative nucleoside product [ 36 ], revealed that the number of 8-OHdG-positive cells increased after UUO surgery (Sham, 1.1 ± 0.4 vs. UUO, 40.3 ± 4.4, p < 0.001) ( Figure 5 D,E). However, CS treatment remarkably reduced the number of 8-OHdG-positive cells (UUO, 40.3 ± 4.4 vs. UUO+CS, 6.4 ± 1.3, p < 0.001) ( Figure 5 D,E).…”
Section: Resultsmentioning
confidence: 99%
“…Renal levels of MDA, another lipid peroxidation product [ 29 ], were also reduced by OXA (CP, 4.5 ± 0.5 nmol/mg protein vs. CP + OXA, 1.8 ± 0.3 nmol/mg protein, p < 0.001) ( Figure 4 C). In addition, OXA reduced renal levels of 8-OHdG, a product of oxidative DNA damage [ 30 ] (CP, 92.6 ± 9.6 ng/g protein vs. CP + OXA, 65.9 ± 6.5 ng/g protein, p < 0.05) ( Figure 4 D). OXA also increased GSH levels (CP, 2.1 ± 0.3 nmol/mg protein vs. CP + OXA, 3.0 ± 0.2 nmol/mg protein, p < 0.01) and GSH/GSSG ratio (CP, 1.1 ± 0.2 vs. CP + OXA, 2.6 ± 0.2, p < 0.001), while decreasing GSSG levels (CP, 1.8 ± 0.2 nmol/mg protein vs. CP + OXA, 1.2 ± 0.2 nmol/mg protein, p < 0.05) ( Figure 4 E–G).…”
Section: Resultsmentioning
confidence: 99%
“…HE‐staining results showed that hispidulin could alleviate renal pathological injury, renal interstitial fibrosis, and inflammatory infiltration in UAN rats. Consistently, in LPS‐induced acute kidney injury mice, hispidulin is determined to ameliorate endotoxin‐induced kidney injury by suppressing inflammation, oxidative stress, and tubular cell death (Kim & Leem, 2022). In addition, hispidulin is also reported to relieve high‐glucose‐induced podocyte injury by regulating protective autophagy (Wu et al., 2018).…”
Section: Discussionmentioning
confidence: 96%